Digital MSME Transformation: The role of strategy e-marketplace mediates the influence of social media promotion and marketing innovation on marketing performance - Santika, I Komang Ari; Suardana, Ida Bagus Raka (International research journal of management, IT and social sciences, 2025)
The development of digital technology has driven transformation in Micro, Small, and Medium Enterprises (MSMEs), which play a strategic role in the Indonesian economy. Despite their significant contribution, most MSMEs still face obstacles in utilizing digital platforms to improve their marketing performance. Social media and marketing innovation are believed to be capable of strengthening the competitiveness of MSMEs, but previous research findings have been inconsistent. This study aims to analyze the influence of social media promotion and marketing innovation on marketing performance, as well as to examine the strategic role of e-marketplace utilization as a mediating variable. The study uses a quantitative approach with a survey method targeting MSME actors in Bali. Data were analyzed using SEM-PLS. The results show that social media promotion and marketing innovation have a positive effect on marketing performance, both directly and through the use of e-marketplaces. In addition, e-marketplaces are proven to be able to mediate the relationship between social media promotion and marketing innovation with the marketing performance of MSMEs. These findings emphasize the importance of utilizing digital platforms as a strategy to increase competitiveness and expand markets.